PEMANFAATAN JERAMI PADI FERMENTASI DENGAN MOD-71 TERHADAP PERFORMANS DOMBA SEI PUTIH JANTAN - firman ketaren (Jurnal Peternakan Integratif, 2013)
This study aims to determine the use of rice straw fermented with various concentration of MOD-71 on feed intake, body weight gain and feed conversion ratio of Sei Putih sheep male. Research was conducted at the Faculty of Agriculture, University of Sumatra Utara from May 2012 up  to August 2012. The design used in this study was a randomized block design (RBD) with 4 treatments and 3 blocks. Which in use 12 sheeps male with initial body weight gain/sheep 10,675 + 0,30 kg, 12,762 + 0,22 kg ,  and + 14,637 + 0,24 kg. The treatment consists of concentration on rice straw were P0 (0 cc/kg); P1(2cc/kg); P2 (4cc/kg); and P3 (6cc/kg). The results showed that administration of fermented straw MOD-71 were not significantly different (P >0,05) on feed intake, body weight gain and feed conversion ratio on Sei Putih sheep male. The results showed the average feed intake is 497,40 (g/head/day), average daily gain is 21,13 (g /head/day), average feed conversion ratio  is 23,58. It can be concluded that the addition of MOD-71 does not effectively improve the quality of rice straw in sei putih sheep male. Keywords: Rice Straw, Fermentation, MOD-71, Sei Putih sheep  male.